Penerapan Kurikulum Campuran (K-13 & Kurikulum Merdeka) di MAN Binjai - Neliwati, Neliwati; Tika, Bunga Ulan; Khoiron, Fitra; Iswani, Juni Tri; Ananta, M. Fadliq (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
The Indonesian education system has undergone many curriculum revisions. The 2013 curriculum is now used as the main curriculum in schools. However, a number of schools use a unique curriculum known as the Independent Curriculum. The aims of this study were to: (1) find out the differences in implementation between the 2013 Curriculum and the Independent Curriculum at MAN BINJAI; (2) comparing the 2013 Curriculum and the Independent Curriculum at MAN BINJAI; and (3) examine the challenges related to the implementation of the 2013 curriculum and the independent curriculum in the classroom. The results of the research show that the implementation of a mixed curriculum can be implemented, but there are still obstacles that must be faced by both teachers and students. So there is still something that needs to be improved in the use of the mixed curriculum.